If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5w + -1)(5 + w) = 0 Reorder the terms: (-1 + 5w)(5 + w) = 0 Multiply (-1 + 5w) * (5 + w) (-1(5 + w) + 5w * (5 + w)) = 0 ((5 * -1 + w * -1) + 5w * (5 + w)) = 0 ((-5 + -1w) + 5w * (5 + w)) = 0 (-5 + -1w + (5 * 5w + w * 5w)) = 0 (-5 + -1w + (25w + 5w2)) = 0 Combine like terms: -1w + 25w = 24w (-5 + 24w + 5w2) = 0 Solving -5 + 24w + 5w2 = 0 Solving for variable 'w'. Factor a trinomial. (-5 + -1w)(1 + -5w) = 0Subproblem 1
Set the factor '(-5 + -1w)' equal to zero and attempt to solve: Simplifying -5 + -1w = 0 Solving -5 + -1w = 0 Move all terms containing w to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -1w = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -1w = 0 + 5 -1w = 0 + 5 Combine like terms: 0 + 5 = 5 -1w = 5 Divide each side by '-1'. w = -5 Simplifying w = -5Subproblem 2
Set the factor '(1 + -5w)' equal to zero and attempt to solve: Simplifying 1 + -5w = 0 Solving 1 + -5w = 0 Move all terms containing w to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -5w = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -5w = 0 + -1 -5w = 0 + -1 Combine like terms: 0 + -1 = -1 -5w = -1 Divide each side by '-5'. w = 0.2 Simplifying w = 0.2Solution
w = {-5, 0.2}
| (2x-3)+1=17 | | 3.5+-9= | | -3(1-4n)=-63 | | y=2*4+2.50*4 | | (7+4w)=13 | | -26+7p=5(3p+6) | | -3(1-4n)=63 | | -3(1-4)=-63 | | 1.5-7= | | y=2(2)+2.50(2) | | 3b+-4=14 | | -15a-a+4=64 | | -21n-15=-82 | | -13a-18=73 | | 21x-28= | | h=-16t^2+16t+112 | | -3(x-1)+8(x-3)=6x-5x | | -5k-7=-37 | | p/2=3/4+p/3 | | x=9x^3-6x^2 | | y=10+-7(0) | | -k-3k-2k=-36 | | -z-4z=-65 | | 3/2x+1/5=3/4 | | y=10-7(-2) | | (0.1x-21)=180 | | 2a^5-8a^4-24a^3= | | 8.2-r=5r | | 15=35x | | -3x(2x+4)=0 | | (48+2x)(72+2x)-3456=0 | | 3a=9b-12 |